The influence of cognitive frame similarity on contingency planning in strategic alliances - Hanisch, Marvin; Haeussler, Carolin; Graf-Vlachy, Lorenz; König, Andreas; Cho, Theresa S. (Academy of Management Annual Meeting Proceedings, 2018)
Contingency planning is central to strategic alliances because it makes partnerships more reliable and predictable. Thus, it is puzzling to see that partners frequently rely on the prospect of good faith negotiations in the future rather than explicit contractual terms to deal with contingencies. We combine contract theory with social cognition theory to resolve this conundrum. Specifically, we introduce the concept of cognitive frame similarly and suggest that partners with higher cognitive frame similarity are more likely to use good faith provisions than partners with lower cognitive frame similarity. This is because partners with higher cognitive frame similarity are more likely to expect that their interpretations of future contingencies correspond, ultimately decreasing the perceived benefits of explicit contingency planning. Additionally, we argue that the relationship between frame similarity and the partners use of good faith is amplified by their structural similarity. We test our framework on a unique dataset based on manual and computer-assisted content analysis of 705 alliance contracts and 1,410 organizational mission statements from the bio-pharmaceutical industry. Our results support our theory, allowing us to highlight the importance of cognitive frames in inter-organizational relationships and to provide novel perspectives to research on strategic alliances and contract design.
CRIS-Team Scopus Importer:2026-04-08